The Potency of Artocarpus Heterophyllus Leaf as a Facial Skin Care Ingredient in Clay Mask Formulation - Widyawati, Tri; Syarifah, Siti; Daulay, Milahayati; Lolyta, Fitri Mustanti (Asian Journal of Pharmaceutical Research and Development, 2019)
Artocarpus heterophyllus (Ah), common name as nangka, has been reported to have antidiabetic, antihyperlipidemia, antimicrobial and antioxidant activity. Balinese women used its leaves for facial treatment. This study aims to evaluate its leaf potency for facial skin care. Ethanol extract of Ah (EEAh) that obtained by maceration was prepared into 3 clay mask formulations (FI: 1%, FII:3% and FIII:5%). F0 was used as control group. A total of 12 volunteers were treated with clay mask to evaluate its effect on moisture and pores size after intervention. The data were analysed using Kruskall Wallis and Mann Whitney test. The results showed that skin moisture increased after intervention (FI:3.7%; FII:4.7%;FIII:7.3%). Pores size decreased in FI (6.3%) and FII (13.4%). Statistically, there were significant different between F0-F1 (p=0.043), F0-F2 and F0-F3 (p=0.046 of each). The present study conclude that clay mask containing A. heterophyllus leaf ethanol extract have potency to be used as facial skin care.